Activities of Administrative Judiciary During Marital State in Ukraine - M. V. Kolesnikova; D. O. Vavilo (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the problem of access to justice in Ukraine under the conditions of martial law that has been ongoing since 2014, in particular after the start of a full-scale invasion of the Russian Federation in 2022. Emphasis is placed on the need to ensure the functioning of the judicial system even in conditions of active hostilities, because according to Article 124 of the Constitution of Ukraine and the Law of Ukraine “On the Legal Regime of Martial Law”, courts are obliged to continue their activities and cannot limit their powers. This issue has become particularly relevant due to the escalation of the conflict and the growing challenges facing the administrative courts, which must ensure access to justice despite logistical and organizational difficulties. The study notes that even in extraordinary legal regimes, according to the recommendations of the Venice Commission, the judicial system must adhere to the principles of a fair trial. The article also analyzes the main problems faced by the administrative judiciary under martial law, in particular, the lack of funding, difficulties in organizing the work of the courts, the movement of participants in the process, and the need to change territorial jurisdiction. On the basis of the conducted analysis, the goals and tasks of the study, as well as proposals for improving administrative proceedings, are formulated. The importance of legislative changes that would allow courts to stop proceedings in cases when the participants cannot be present due to the circumstances of the war, as well as the need to ensure the rights and freedoms of citizens who find themselves in hostilities, is emphasized. The article emphasizes that administrative justice under martial law needs greater flexibility and adaptability to effectively resolve legal issues arising in this critical period. Thus, the study contributes to the study of the impact of the war on the legal system of Ukraine and emphasizes the need to preserve justice in constantly changing conditions.